2018
DOI: 10.15395/mkb.v50n3.1320
|View full text |Cite
|
Sign up to set email alerts
|

Potensi Fraksinasi Sarang Semut Papua (Myrmecodia pendans) pada Penurunan TNF-α dan Perbaikan Secara Histopatologi Kartilago Osteoartritis Lutut Kelinci

Abstract: Reaksi seluler kondrosit osteoartritis pada lutut ditandai dengan peningkatan sitokin tumor necrosis factor-α (TNF-α).TNF-α mengaktifkan fibroblas dan makrofag sinovial untuk menyekresi enzim degradasi dan menekan sintesis proteoglikan rawan sendi sehingga memberikan gambaran histopatologik kartilago yang mengalami perubahan. Osteoartritis sekunder terjadi akibat trauma sendi yang menyebabkan nyeri. Terapi obat seperti non-steroidal anti-inflammatory drugs (NSAIDs) yang digunakan menyebabkan efek samping merug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
1
0
2
Order By: Relevance
“…The potential of Sarang Semut (Myrmecodia pendans) as an alternative treatment is proven to be accurate (p < 0.05) and can inhibit the growth of Streptococcus sanguinis bacteria (batresiotatis) in dental therapy (Soviati et al, 2022). The results of other studies in vitro showed that fractionation of anthill plants (Myrmecodia pendans ) was able to reduce TNF-α (p = 0.011) and histopathological improvement in cases of osteoarthritis cartilage (p = 0.034) (Hidajat et al, 2018). The results of other experiments showed that anthills (Myrmecodia pendants) as a food additive also produced a high antioxidant potential of 85.90%, even offered to have antibacterial activity against five types of bacteria (Escherichia coli ATCC 25922, Staphylococcus aureus ATCC 6538, Streptococcus mutans ATCC 25175, Pseudomonas aeruginosa ATCC 9027, Salmonella typhimurium ATCC 14028) with an inhibitory zone of 10-13.5 mm (Khairiah et al, 2019).…”
Section: Introductionmentioning
confidence: 92%
“…The potential of Sarang Semut (Myrmecodia pendans) as an alternative treatment is proven to be accurate (p < 0.05) and can inhibit the growth of Streptococcus sanguinis bacteria (batresiotatis) in dental therapy (Soviati et al, 2022). The results of other studies in vitro showed that fractionation of anthill plants (Myrmecodia pendans ) was able to reduce TNF-α (p = 0.011) and histopathological improvement in cases of osteoarthritis cartilage (p = 0.034) (Hidajat et al, 2018). The results of other experiments showed that anthills (Myrmecodia pendants) as a food additive also produced a high antioxidant potential of 85.90%, even offered to have antibacterial activity against five types of bacteria (Escherichia coli ATCC 25922, Staphylococcus aureus ATCC 6538, Streptococcus mutans ATCC 25175, Pseudomonas aeruginosa ATCC 9027, Salmonella typhimurium ATCC 14028) with an inhibitory zone of 10-13.5 mm (Khairiah et al, 2019).…”
Section: Introductionmentioning
confidence: 92%
“…7 Thus, Nucky et al, showed that the ethanol extract of M. pendans had an anti-inflammatory effect by decreasing levels of the inflammatory mediator TNF-α in the blood in which phytochemical compounds from the fractioned extract were flavonoids. 22 As shown in Figure 1A, the black arrow indicates that part of the colon that has epithelial erosions that is seen at 40x magnification. Normal: There were no erosions in the colonic epithelium; CC: There were erosions> ½ of the thickness of the mucosa + area of damage <50%; MPE100 and MPE200: Erosion <½ of mucosal thickness + area of damage <25%.…”
Section: The Effect Of Mpe On Inflammatory Cell Infiltration Scorementioning
confidence: 98%
“…Sarang semut (family: Rubiaceae) adalah tanaman epifit yang hidupnya menempel pada tumbuhan lain (Dirgantara et al, 2015;Hidajat et al, 2018;Safniyeti, 2017). Tanaman ini kemudian menjadi tempat semut untuk bersarang.…”
Section: Pendahuluanunclassified